Correlation between Low Birthweight and Underweight in Children Under Five: A Meta-Analysis - Nurfitria, Adilla Misi; Raharjo, Setyo Sri; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Underweight among children results in growth disorders, and stunting. The study aims to determine the correlation between low birthweight and underweight in children under five based on primary studies previously conducted. Subjects and Methods: This study used a meta-analysis study with PICO as follows: P=chidren under five, I= low birthweight, C= normal birthweight, O= underweight. The search for articles in this study used databases, namely Pubmed, Google Scholar, and Springerlink. The article search used the following keywords: Low birth weight AND underweight OR underweight toddler AND low birthweight. The articles were analyzed by using Review Manager 5.3. Results: There were 9 articles from Ghana, Bangladesh, East Kenya, Pakistan, Malawi, China, Ethiopia, and Rwanda from 2017-2022 analyzed by using PRISMA flow diagrams. These results indicated that children under five with a history of low birthweight had 2.21 times risk of being underweight compared to children under five who had a history of normal birthweight (aOR= 2.21; CI 95% = 1.96 to 2.49; p<0.001). Conclusion: Children under five with low birthweight history are at risk of being underweight. Keywords: low birthweight, underweight, children under five, meta-analysis Correspondence: Adilla Misi Nurfitria. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A Surakarta 57126, Central Java, Indonesia. Email: Adillamisi2502@gmail.com. Mobile: +6285786605313.